A novel and efficient synthesis of 2-substituted quinazolin-4(3H)-ones by the reaction of (het)arylmethanamines with isatoic anhydride. Issue 33 (17th August 2016) - Mahdavi, Mohammad; Hassanzadeh, Rasool; Soheilizad, Mehdi; Golshani, Shiva; Moghimi, Setareh; Firoozpour, Loghman; Shafiee, Abbas; Foroumadi, Alireza
Graphical abstract: Highlights: Quinazolin-4(3 H )-ones were synthesized in a one-pot reaction. The reaction proceeded in the presence of catalytic CuBr under aerobic conditions. Good yield and broad substrate scope are the advantageous features. Abstract: A novel and straightforward method for the synthesis of quinazolin-4(3 H )-ones is described. The one-pot reaction between isatoic anhydride and (het)arylmethanamines led to the formation of N -substituted anthranilamides, which under aerobic conditions in the presence of CuBr undergo an in situ oxidation–cyclization reaction to produce quinazolin-4(3 H )-ones in good yields.